1977
DOI: 10.1007/bf00996319
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon levels in normal and diabetic subjects: Use of a specific immunoabsorbent for glucagon radioimmunoassay

Abstract: Summary.Non-specific plasma effects may produce major errors in the estimation of true plasma pancreatic glucagon concentrations by radioimmunoassay. This has been circumvented by the production of glucagon-free plasma for each individual investigated, by means of glucagon antibody, coupled to sepharose beads. True fasting pancreatic glucagon levels (mean _+ SEM) in 18 healthy subjects (24 +_ 3 pg/ml) were significantly lower (p < 0.005) than in 10 non-ketotic non-obese diabetics (38 + 3 pg/ml). It is suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(37 citation statements)
references
References 21 publications
(31 reference statements)
0
36
0
1
Order By: Relevance
“…However, the physiological concentration of glucagon released in islet secretions is less than 17 pM, which is lower than the detection limit of the sensor, and its influence was considered insignificant. [49][50] The concentration levels of amylin and somatostatin in the islet secretion are also very small, about 1/100 and 1/25 of the insulin concentration, respectively. [51][52] And, pancreatic polypeptide does not show the Raman peak at 1002 cm -1 from phenylalanine.…”
mentioning
confidence: 99%
“…However, the physiological concentration of glucagon released in islet secretions is less than 17 pM, which is lower than the detection limit of the sensor, and its influence was considered insignificant. [49][50] The concentration levels of amylin and somatostatin in the islet secretion are also very small, about 1/100 and 1/25 of the insulin concentration, respectively. [51][52] And, pancreatic polypeptide does not show the Raman peak at 1002 cm -1 from phenylalanine.…”
mentioning
confidence: 99%
“…Glucagon was measured by radioimmunoassay (Alford et al, 1977), cAMP was assayed by saturation analysis (Brown et al, 1971) and noradrenaline and adrenaline by COMT radioenzymatic assay (Brown et al, 1981). Blood glucose was measured by a glucose oxidase method using an auto-analyser.…”
Section: Methodsmentioning
confidence: 99%
“…Further studies are needed to determine whether glucagon [20][21][22][23][24][25][26][27][28][29] bonds [33] . However other studies have suggested that IDE cleaves at Arg 17 -Arg 18 bonds with the formation of glucagon [18][19][20][21][22][23][24][25][26][27][28][29] , which may then be converted into glucagon [19][20][21][22][23][24][25][26][27][28][29] by an unidentified aminopeptidase like enzyme [34] . It is possible that such residual hepatocyte enzymes are present in plasma leading to the formation of glucagon [19][20][21][22][23][24][25][26][27][28][29] , and perhaps lead to the formation of glucagon [20]…”
Section: Figurementioning
confidence: 99%
“…Glucagon [1][2][3][4][5][6][7][8][9][10][11][12][13] and glucagon [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] , and the minor metabolites glucagon [1][2][3][4][5][6][7][8][9][10] , glucagon [14][15][16][17][18][19][20][21][22][23][24][25] and glucagon [23][24]…”
Section: Introductionunclassified
See 1 more Smart Citation